PENERAPAN GREEN BUDGETING DALAM PERENCANAAN ANGGARAN UNTUK MENDUKUNG PEMBANGUNAN BERKELANJUTAN (STUDI PADA DLHK DIY) - Astrid Cintya Putri; Mia Rosmiati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the implementation of green budgeting in budget planning to support sustainable development at the Environmental and Forestry Agency (DLHK) of the Special Region of Yogyakarta. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and document analysis. The findings indicate that the implementation of green budgeting in DLHK DIY is still at an early stage and has not been systematically integrated into the regional budgeting process. Although environmental aspects have been incorporated into planning documents and supported by instruments such as climate budget tagging, environmental indicators, and monitoring systems, their utilization remains limited and has not fully supported evidence-based decision-making. The main challenges include limited budget allocation, data availability, human resource capacity, and suboptimal coordination among government agencies. In addition, the absence of a structured green budgeting framework hinders the comprehensive integration of environmental aspects into the budgeting cycle. Despite these limitations, existing budget planning has contributed to sustainable development, particularly in waste management and pollution control. Therefore, strengthening the integration of policy, budgeting, and program implementation is necessary to enhance the effectiveness of green budgeting. This highlights the need for a transformation in budget governance that is more integrated, adaptive, and oriented toward environmental performance. Consequently, green budgeting should not only function as an administrative tool but also as a strategic policy instrument in improving environmental quality in a sustainable manner.